THE BEHAVIOR ANALYSIS GENERATION Y IN USING SEARCH ENGINE FOR TRAVEL PURPOSES - Mohamad Yusop, Nur Dalila Binti; Mohd Zin, Maizatul Anis Asyikin Binti; Kurniawan, Ikhsan; Girinsah, . (Universitas Pendidikan Indonesia, 2015)
Technology changes every day and makes life easier. Related to this, the purpose of this research is to identify the characteristics or behavior analysis of Generation Y in using search engine for travel purposes.By definition, Gen Ys or Millennial Generation are those young people who were born between the year of 1990 to 2000. They are also the first generation to have spend their entire life in the digital environment. Nowadays, we could find Gen Ys actively contributes, shares, searches for tourism purposes. The research is focus on the tendency and preferences of the youngsters who are willingly go to travelling website and looking for information before travel. The research method in this study is survey research. The research object is students who were categorized as Gen Y at Universitas Pendidikan Indonesia (UPI) and Universiti Teknologi Mara (UiTM) Malaysia. The respondents were sent an email message describing the study and inviting them to participate via online questionnaire using Google Form. Through this method the sample and data were collected. Study results would be expected to discover their behaviour in using the search engine before travelling. This study is also expected to give a huge impact on how to spread the information about travel and tourism industry such as tourist attraction, accommodation, transportation and culinary arts preferences. In a separate discussion about the future of the world, it was clear the Gen Ys are generally well equipped to deal with the leadership and societal challenges we all will be facing in the near future.